Parameters affecting thixotropic behavior of self compacting concrete and 3D printable concrete; a state-of-the-art review. (11th July 2022) - Biricik, Öznur; Mardani, Ali
Highlights: Thixotropy occurs as a result of aggregation and chemicals bonds between particles. Thixotropic behavior is very important in self-compacting and 3-dimensional concrete. Thixotropy affects pumpability, hydrostatic pressure of concrete. Cement, mineral, chemical admixture, aggregate based parameters affect thixotropy. Abstract: Structural changes as a result of thixotropic behavior are very important in cementitious systems such as self-compacting concrete (SCC) and 3-dimensional concrete (3D) mixtures with high binder volume. In this context, it was understood that the examination of the parameters affecting the thixotropy behavior of cementitious systems is realized by measuring the time-dependent change of the rheological properties of the mixture. For this purpose, it was understood that rheometer, measurement and comparison methods, which are quite different from each other, are used. In this study, the parameters affecting the thixotropic properties of cementitious systems; the parameters originating from cement, mineral-chemical admixtures, aggregate and mixture properties (water/binder (w/b) ratio and mixing process) were examined under the headings. In addition to these, the rheometer, measurement and evaluation methods used in the studies were examined. It was stated that the interaction between particles, bond strength of particles, flocculation and thixotropic change rate increase with the increase of cement fineness, alkali and C3 A ratio. It was emphasized that the thixotropic property of the mixture increased with the use of mineral additives such as silica fume, limestone dust and blast furnace slag, and the reverse of this behavior was observed when fly ash was used. It was reported that the addition of clay and calcined clay to cementitious systems increases the thixotropic behavior due to its layered structure. It was emphasized that the structural build-up of cementitious systems decreases with the addition of water reducer admixtures, and increases with the addition of viscosity modifying admixtures.